The association between alexithymia as assessed by the 20-item Toronto Alexithymia Scale and depression: A meta-analysis - Li, Shuwen; Zhang, Bin; Guo, Yufang; Zhang, Jingping (Psychiatry research, 2015)
Patients with depression exhibit high rates of alexithymia, representing a major public health concern. We sought to examine relationships between depression severity and alexithymia as assessed by the Toronto Alexithymia Scale (TAS-20) and the TAS-20 subscales of difficulty identifying feelings (DIF), difficulty describing feelings (DDF), and externally oriented thinking (EOT). Potentially relevant studies were obtained independently by two reviewers. Chi-square statistics based on the Q-test and I2 index assessed statistical heterogeneity between studies. Subgroup analyses were mainly used to explore sources of heterogeneity. Begg׳s test and Duval and Tweedie’ trim and fill were used to assess potential publication bias. Altogether, 3572 subjects from 20 study groups across 19 studies were included. Medium relationships were observed between depression and TAS-total score (TAS-TS), DIF, and DDF. There was also a weak relationship between EOT and depression. Subgroup analyses showed a stronger correlation between TAS-TS and depression assessed by self-reported tools than that assessed by the Hamilton Rating Scale for Depression. The heterogeneity significantly decreased only in the subgroup analysis by depression tool. We conclude that alexithymia, as assessed by the TAS-20 and its subscales DIF and DDF, is closely related to depression. These relationships were affected by depression measurement tools. •The TAS-20 and its subscales DIF and DDF were moderately related to depression severity.•The subscale EOT was weakly related to depression.•Assessment tool for depression was important in the association between alexithymia and depression.